High-density lipoprotein subpopulation profiles in lipoprotein lipase and hepatic lipase deficiency. (October 2016) - Tani, Mariko; Horvath, Katalin V.; Lamarche, Benoit; Couture, Patrick; Burnett, John R.; Schaefer, Ernst J.; Asztalos, Bela F.
Abstract: Background and aims: Our aim was to gain insight into the role that lipoprotein lipase (LPL) and hepatic lipase (HL) plays in HDL metabolism and to better understand LPL- and HL-deficiency states. Methods: We examined the apolipoprotein (apo) A-I-, A-II-, A-IV-, C-I-, C-III-, and E-containing HDL subpopulation profiles, assessed by native 2-dimensional gel-electrophoresis and immunoblotting, in 6 homozygous and 11 heterozygous LPL-deficient, 6 homozygous and 4 heterozygous HL-deficient, and 50 control subjects. Results: LPL-deficient homozygotes had marked hypertriglyceridemia and significant decreases in LDL-C, HDL-C, and apoA-I. Their apoA-I-containing HDL subpopulation profile was shifted toward small HDL particles compared to controls. HL-deficient homozygotes had moderate hypertriglyceridemia, modest increases in LDL-C and HDL-C level, but normal apoA-I concentration. HL-deficient homozygotes had a unique distribution of apoA-I-containing HDL particles. The normally apoA-I:A-II, intermediate-size (α-2 and α-3) particles were significantly decreased, while the normally apoA-I only (very large α-1, small α-4, and very small preβ-1) particles were significantly elevated. In contrast to control subjects, the very large α-1 particles of HL-deficient homozygotes were enriched in apoA-II. Homozygous LPL- and HL-deficient subjects also had abnormal distributions of apo C-I, C-III, and E in HDL particles. Values for all measured parameters in LPL- and HL-deficient heterozygotes were closer to values measured in controls than in homozygotes. Conclusions: Our data are consistent with the concept that LPL is important for the maturation of small discoidal HDL particles into large spherical HDL particles, while HL is important for HDL remodeling of very large HDL particles into intermediate-size HDL particles. Highlights: Lipoprotein lipase is necessary for the maturation of small lipid-poor HDL into larger more complex HDL particles. Hepatic lipase helps remodeling large HDL particles into smaller less complex HDL particles. HDL metabolism is not a simple, linear size-expansion of HDL particles.